CORPORATE FINANCIAL DISTRESS AND BANKRUPTCY: A COMPARATIVE ANALYSIS IN FRANCE, ITALY AND SPAIN - Alessandra Amendola; Marialuisa Restaino; Luca Sensini (Global Economic Observer)
The paper presents a competing-risks approach for investigating the determinants of corporate financial distress. In particular a comparative analysis of three European markets-France, Italy and Spain–is performed in order to find out the similarities and the differences in the determinants of distress.By using the AMADEUS dataset, two possible causes of exit from the market are considered:bankruptcy and liquidation. For identifying the variables that influence the risk of leaving the market,a competing-risks model for each country is estimated and is compared with a pooled model including all the three countries. In addition, the performance of the competing-risks approach is evaluated versus the single-risk model, in which all states are considered without any distinctions.The reached results show that the competing risks approach leads to a saving in the number of selected variables that becomes more significant when the model is estimated for each country separately. Moreover, the selected variables for each country enable to identify similarities between the different exit routes across the markets. Some of the differences between Spain and the other two countries may be related to the dissimilar definition of the distress states.